Dual‐Mode Optical Thermometers Based on the Thermal‐Stable Perovskite Nanocrystals Embedded in Robust Metal Halide Salts - Dandan Yang; Tianzhu Zhao; Zixing Peng; Xiudi Xiao; Guoping Dong (Advanced Physics Research)
Abstract Photothermal sensing is crucial for the creation of smart integrated devices. All‐inorganic metal halide perovskites with the formula CsPbX3 (X═Cl, Br, I) have excellent photo‐physical performance, offering exciting opportunities for flexible electronics. Hence, a supersaturated precipitation strategy is proposed for the preparation of salt‐shelled metal halide solids. The well‐designed CsPbX3@MX (M═K, Cs) products exhibit bright narrow visible emissions and favorable thermal stability up to 195 °C. Co‐doping with Ni2+ and Mn2+ ions, the CsPbCl3@KCl products have realized dual‐mode thermometry. Utilizing the blue emission from the CsPbCl3 host and the red emission from the Mn2+ ion, a fluorescence intensity ratio technique is obtained to monitor the temperature of good stability and repeatability. Based on the regular fluorescence decay of Mn2+ ions with rising temperature, the lifetime of Mn2+ ions can also be used for temperature sensing. It is believed that such stable metal halides with dual‐mode thermometry will provide a new sight for optical thermometers and, more importantly, will unleash the possibility of a broad variety of applications in lightweight and integrated functional devices.